Georgia Architectural and Historic Properties Survey of Quitman [399] 405 E. Swamp St. Valdosta, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Quitman [399] 405 E. Swamp St. Valdosta, Ga. December 1980. One story double pen house; gabled, tin roof. Shed porch with square posts (screened). Clapboard siding. Exterior chimney. Bay at right front. Sash windows with 2/2 lights. Set on brick piers. Fair condition. Date of Construction: c. 1910. This area developed from app. 1900-1920 by black residents. Significant as part of a potential National Register historic district, bound by Court St. on the west and the SCL tracks on the north.
1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.15 MB (1,207,499 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Quitman (Ga.)